Eu:CROPIS - "Euglena gracilis: Combined Regenerative Organic-food Production in Space" - A Space Experiment Testing Biological Life Support Systems Under Lunar And Martian Gravity - Hauslage, Jens; Strauch, Sebastian; Essmann, Olaf; Haag, Ferdinand; Richter, Peter; Krüger, Julia; Stoltze, Julia; Becker, Ina; Nasir, Adeel; Bornemann, Gerhild; Mueller, Hartmut; Delovski, Toni; et al. (Microgravity Science and Technology, 2018)
Human space exploration needs stable life support systems for the supply of oxygen, water and food for each human explorer due to long term missions. The most promising approach for building stable life support systems is a combination of physico-chemical and biological systems. These hybrid systems combine the reliability of physico-chemical and the sustainability of biological life support systems. Also the disadvantages, which are the finite resources of physico-chemical and the imperfect reliability of biological systems, are mutually balanced. To improve the reliability of biological life support systems, a combination of different biological systems may stabilize the whole approach during long term operations. The satellite mission Eu:CROPIS (Euglena gracilis: Combined Regenerative Organic-food Production In Space) is a testbed for investigating the behavior of combined biological life support systems under the influence of altered gravity, here, Lunar and Martian gravity. The core systems are a biological trickle filter for processing urine into a fertilizer solution via nitrification and Euglena gracilis, a photosynthetic protist which is able to produce oxygen and biomass while protecting the whole system against high ammonia concentrations.
Keywords: Compact satellite; Life support system; Moon; Mars; Reduced gravity; Nitrification